2022
DOI: 10.1108/ecam-11-2021-0996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of barriers, benefits and opportunities of using bamboo materials for structural purposes

Abstract: PurposeBamboo is still a traditional material that requires additional development before it can be considered as a modern and reliable alternative to steel, wood, and concrete. When compared to the huge volumes of information available on timber and concrete, bamboo has a little quantity of information. When it comes to estimating bamboo structures, there are not many options. As a result, pinpointing the key qualities and events that aid or impede bamboo's integration into the construction sector is vital.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Applied as a non-structural material in the form of furniture and indoor flooring, and as a heavy-duty material in the form of lumber, bamboo products have excellent performance including high strength and ease of processing [1,2]. Bamboo contains some amounts of sarch, protein and reducing sugars, which are the nutritional foundation of bamboo-decaying mould [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Applied as a non-structural material in the form of furniture and indoor flooring, and as a heavy-duty material in the form of lumber, bamboo products have excellent performance including high strength and ease of processing [1,2]. Bamboo contains some amounts of sarch, protein and reducing sugars, which are the nutritional foundation of bamboo-decaying mould [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo's rapid growth, excellent mechanical properties, and abundant availability position it as an excellent alternative material for wood, which is in short supply [1,2]. Bamboo-wood composites have found extensive applications in container flooring, furniture, and construction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hailemariam et al [ 18 ] identified barriers, benefits, and opportunities of using bamboo materials for structural purposes. A significant barrier obstructing the use of bamboo for structural elements is the difficulty in standardizing it, as with steel or concrete.…”
Section: Introductionmentioning
confidence: 99%